Pengembangan e-Modul Berbasis Pendekatan STEM dan Etnosains Menggunakan Google Sites pada Materi Asam Basa - Greace Astrid Rotua Hutabarat; Makharany Dalimunthe (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to develop an e-module based on STEM and ethnoscience approaches using Google Sites on acid-base material, as well as to determine the feasibility, student responses, and improvement of student learning outcomes at St. Maria Tarutung Private High School. The study was conducted in class XI B MIPA in the 2025/2026 Academic Year. The method used is Research and Development (R&D) with the ADDIE development model consisting of the stages of analysis, design, development, implementation, and evaluation. The research sample consisted of 33 students of class XI B who participated in learning using the developed e-module. The validation results showed that the e-module obtained an average score of 89% from material experts, and 87% from media experts with a very valid category. Student responses to the e-module reached an average of 89.43% with a very practical category. The effectiveness of the e-module is shown through an increase in learning outcomes with an average pre-test score of 48.30 and a post-test of 87.58 and an N-Gain of 0.73 which is included in the high category. The conclusion of this study indicates that the e-module based on the STEM and ethnoscience approaches through Google Sites meets the criteria of validity, practicality, and effectiveness in improving student learning outcomes in acid-base topics.